Do clusters matter for foreign subsidiaries in the Era of industry 4.0? The case of the aviation valley in Poland - Barbara Jankowska; Eleonora Di Maria; Joanna Cygler (European Research on Management and Business Economics (ERMBE), 2021)
Many scholars underline the significance of clusters for knowledge spillovers and related benefits in terms of innovation and firm competitiveness. The Industry 4.0 technological scenario emphasizes dispersed technologically interconnected activities and distributed knowledge management opportunities, while clusters focus on proximity, which is why many question the attractiveness of the latter for firms. Bearing in mind the scarcity of studies on the relationship between digitalization and clusters, the paper discusses how clusters may be attractive for foreign subsidiaries in times of the fourth industrial revolution by referring to the case of the Aviation Valley in Poland as explanatory example supporting conceptual considerations proposed.
Keywords: L1; L2; M2; O3; R3; 650; Cluster; Foreign subsidiary; Industry 4.0; Aviation; Poland